Staff support in a National Health Service mental health trust in response to the COVID-19 pandemic: qualitative study. Issue 2 (16th March 2022) - Smith, Holly; Zhang, Shuo; Jones, Abbeygail; Dorrington, Sarah; Winter, Helen; Beck, Alison
Abstract : Background: The COVID-19 pandemic has highlighted the impact work can have on healthcare workers and the importance of staff support services. Rapid guidance was published to encourage preventive and responsive support for healthcare workers. Aims: To understand mental healthcare staff's help-seeking behaviours and access to support at work in response to the COVID-19 pandemic, to inform iterative improvements to provision of staff support. Method: We conducted a formative appraisal of access to support and support needs of staff in a National Health Service mental health trust. This involved 11 semi-structured individual interviews using a topic guide. Five virtual staff forums were additional sources of data. Reflexive thematic analysis was used to identify key themes. Results: Peer-based, within-team support was highly valued and sought after. However, access to support was negatively affected by work pressures, physical distancing and perceived cultural barriers. Conclusions: Healthcare organisations need to help colleagues to support each other by facilitating open, diverse workplace cultures and providing easily accessible, safe and reflective spaces. Future research should evaluate support in the evolving work contexts imposed by COVID-19 to inform interventions that account for differences across healthcare workforces.